Transdisciplinary vision of digital architecture through computational methods of mapping, analysis and visualization - Correia, R. M. (ISTAR-IUL Winter School 2018 Applied Transdisciplinary Research, 2018)
Architectural practice is changing not only with computers but also with the use of other disciplines. It is important to establish how architecture started to change. This research aims to draw a historic perspective of transdisciplinary digital architecture through the work of key personalities by establishing links between them and their relevance to nowadays architecture.